Injury prevention: knees - Brandon, R.
Women suffer more non-contact ACL tears than men. This is because of anatomical and physiological differences that predispose women to having internal rotation forces at the knee which makes them more vulnerable to ACL tears during landing and cutting movements. In addition, women are not as strong as men, which potentially leads to less control of the knee and more internal rotation.